Potential Anti-Senescence Effect of Extract from Andrographis paniculata Herbal Plant and Its Bioactive Compounds: A Systematic Review - Khatimah, Nurul Gusti; Arozal, Wawaimuli; Barinda, Agian Jeffilano; Antarianto, Radiana Dhewayani; Hardiany, Novi Silvia; Shimizu, Ippei; Fadhillah, Muhamad Rizqy (Cell and BioPharmaceutical Institute, 2024)
The rapid aging of the global population is a major worldwide issue because of the close relationship between age and the development of several diseases. Aging or senescence is among the most widely studied topics at the moment. However, no pharmaceuticals have been developed that claim to possess anti-senescence properties. Andrographis paniculata, is a medicinal plant found widely throughout tropical and subtropical Asia. This review aims to identify the potential anti- senescence effect of A. paniculata extract and its bioactive compounds. By following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, five databases were used and in vivo and in vitro studies were included in this review. A. paniculata extracts and their bioactive compounds exert anti-senescence properties through their anti-inflammatory and antioxidant properties. This herb and its compounds enhanced memory, cognitive function and behaviour in Alzheimer's disease. The extract also promoted cell cycle progression and proliferation in the skin. In addition, andrographolide exhibited anti-senescence effects in endothelial cells through the activation of PI3K/Akt/Nrf and PI3K/Akt/AP-1 pathways. A. paniculata along with its bioactive compounds including andrographolide and 14-deoxyandrographolide, may have the potential to be used as anti-senescence through anti-inflammatory and antioxidant properties. However, the specific markers to evaluate the senescence are necessary to be conducted. Any clinical trials should be done to establish these findings. Since in clinical settings this potential herbal may be used for long-life time, the safety profile and toxicity of A. paniculata should be considered. Keywords: herbal plants, Andrographis paniculata, andrographolide, bioactive compounds, senescence